Modulation of growth cone filopodial length by carbon monoxide. Issue 6 (22nd August 2016) - Estes, Stephen; Artinian, Liana; Rehder, Vincent
ABSTRACT: Carbon monoxide (CO) is physiologically produced via heme degradation by heme oxygenase enzymes. Whereas CO has been identified as an important physiological signaling molecule, the roles it plays in neuronal development and regeneration are poorly understood. During these events, growth cones guide axons through a rich cellular environment to locate target cells and establish synaptic connections. Previously, we have shown that another gaseous signaling molecule, nitric oxide (NO), has potent effects on growth cone motility. With NO and CO sharing similar cellular targets, we wanted to determine whether CO affected growth cone motility as well. We assessed how CO affected growth cone filopodial length and determined the signaling pathway by which this effect was mediated. Using two well‐characterized neurons from the freshwater snail, Helisoma trivolvis, it was found that the CO donor, carbon monoxide releasing molecule‐2 (CORM‐2), increased filopodial length. CO utilized a signaling pathway that involved the activation of soluble guanylyl cyclase, protein kinase G, and ryanodine receptors. While increases in filopodial length often occur from robust increases in intracellular calcium levels, the timing in which CO increased filopodial length corresponded with low basal calcium levels in growth cones. Taken together with findings of a heme oxygenase‐like protein in the Helisoma nervous system, these results provide evidence for CO as a modulator of growth cone motility and implicate CO as a neuromodulatory signal during neuronal development and/or regeneration. © 2016 Wiley Periodicals, Inc. Develop Neurobiol 77: 677–690, 2017